2019
DOI: 10.4143/crt.2017.595
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Eighth American Joint Committee on Cancer Staging System for Distal Bile Duct Carcinoma

Abstract: The T and N categories of the eighth edition AJCC staging system for DBDC accurately predict patient prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…TNM staging is the most widely accepted and clinically used system in determining the prognosis of cancers occurring in almost all gastrointestinal tracts. Recently, the eighth edition of the AJCC TNM classification was published, and a retrospective single center study was conducted to validate the changed staging system for DCC [7]. In the study, the application of T category defined by DOI and N category with three-tier classification showed better separation of survival curves of each prognostic group than the conventional system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TNM staging is the most widely accepted and clinically used system in determining the prognosis of cancers occurring in almost all gastrointestinal tracts. Recently, the eighth edition of the AJCC TNM classification was published, and a retrospective single center study was conducted to validate the changed staging system for DCC [7]. In the study, the application of T category defined by DOI and N category with three-tier classification showed better separation of survival curves of each prognostic group than the conventional system.…”
Section: Discussionmentioning
confidence: 99%
“…When classified by the AJCC 7th edition, 159 patients (67.7%) were classified as T3. The median TLNC and PLNC were 18 (1-64) and 2 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), and the median LNR values obtained by using these two values were 0.11 (0.02-1.00). In the 7th AJCC classification, 78 patients were classified as N1.…”
Section: Patient Characteristicsmentioning
confidence: 96%
See 1 more Smart Citation
“…[6][7][8][9] From the 7th edition onwards, gallbladder invasions were not considered as belonging to the T category for perihilar bile duct cancers and remained as T3 for DBDCs. 1,2 Although gallbladder invasions have traditionally been accepted as a component of the T category-related factors of DBDC, previous studies have not demonstrated the survival effects of gallbladder invasions in DBDC (Table 3). [10][11][12][13][14][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] Moreover, no single gallbladder invasion was reported in 1543 cases from 23 previous studies of DBDCs.…”
Section: Multivariate Analysismentioning
confidence: 99%
“…2020;144:755-763; doi: 10.5858/ arpa.2019-0218-OA) B ile duct carcinomas (also known as cholangiocarcinomas) comprise 3% of all gastrointestinal cancers globally. 1 Bile duct carcinomas are classified as intrahepatic or extrahepatic bile duct (EBD) carcinomas, and EBD carcinomas are further subclassified as perihilar or distal bile duct carcinomas (DBDCs). 2 It was estimated that 10,910 Americans would be diagnosed with EBD or gallbladder carcinomas in 2015.…”
mentioning
confidence: 99%